Preparation method of personalized composite guided bone regeneration membrane with semi-permeability

The personalized GBR film model is designed through CT scanning technology, and the semi-permeable composite GBR film is manufactured in combination with laser selection melting and electrodeposition technology, which solves the problems of poor rigidity and personalized manufacturing of GBR film materials, achieving efficient and safe bone regeneration effect.

CN119607271APending Publication Date: 2025-03-14CENT SOUTH UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411716765.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

GBR membranes have insufficient bone mass, poor material rigidity, secondary surgery and personalized manufacturing challenges.

Method used

The patient's alveolar bone morphology was obtained by CT scanning technology, a personalized GBR membrane model was designed, and metal porous GBR membranes were manufactured through laser selection melting additive manufacturing technology, and polymer frozen gel was coated using electrodeposition technology to optimize the electrodeposition process to achieve semi-permeability of the composite GBR membrane.

Benefits of technology

A personalized composite GBR membrane with tailored structure, significant osteogenesis and antibacterial capabilities was prepared, which realized semi-permeability, simplified the preparation process, reduced production costs, and improved production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607271A_ABST
    Figure CN119607271A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a personalized composite guided bone regeneration membrane with semi-permeability, and belongs to the field of additive manufacturing of biological materials. A preparation method of a personalized composite guided bone regeneration membrane with semi-permeability comprises the following steps: S1, acquiring an alveolar bone form of a patient by using a CT scanning technology, and designing a personalized GBR membrane model; s2, based on the curved surface features of the personalized GBR membrane model, filling is performed by adopting a plurality of dot matrix units, and a porous GBR membrane model is constructed; s3, the constructed porous GBR film model is imported into selective laser melting additive manufacturing equipment software, and a metal porous GBR film is manufactured; s4, taking the metal porous GBR film formed in the step S3 as a substrate, and coating the metal porous GBR film with polymer frozen gel by using an electro-deposition technology to prepare a composite GBR film; and S5, regulating and controlling the porous structure characteristics of the composite GBR film by optimizing the polymer concentration, the electric field and the electro-deposition time in the electro-deposition process, so as to realize the semi-permeable function of the composite GBR film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomaterial additive manufacturing, and in particular to a method for preparing a semi-permeable personalized composite guided bone regeneration membrane. Background Art

[0002] Dental implants have completely changed the way of repairing missing teeth and significantly improved people's quality of life. However, the implant site is often accompanied by insufficient or severe alveolar bone loss, which is usually related to systemic diseases, periodontal diseases, trauma or tumors. Guided bone regeneration (GBR) technology is one of the main methods for repairing alveolar bone defects. The key is to use GBR barrier membranes to prevent non-osteoblasts from entering the bone defect area, create a favorable growth environment for bone tissue regeneration, and allow osteoblasts to grow without competition. Polymer materials (such as collagen) are commonly used candidate materials for GBR membranes, but due to their lack of rigidity, they are limited to applications in small alveolar bone defects that do not require additional fixation and spatial stability. Therefore, degradable metal-based GBR membranes with good mechanical properties can provide stable spatial support for bone defect areas and do not require secondary surgery to remove them. They are advocated for use in severe and complex alveolar bone defect areas.

[0003] With the increase in clinical needs and the development of digital technology, the use of additive manufacturing processes (such as laser selective melting, SLM) to prepare personalized metal GBR membranes has become a research trend. Additively manufactured personalized metal GBR membranes can shorten surgical time, improve surgical accuracy and reduce the incidence of complications. Electrodeposition is an emerging additive manufacturing method that applies spatiotemporal electrical signals to guide polymer assembly on any conductive metal-based surface, which has versatility in using metal substrates as templates to manufacture various materials (such as gels / coatings / membranes) with complex shapes.

[0004] The study found that polymer materials can form polyelectrolytes in precursor solutions, which are co-deposited and electrodeposited into independent cryogel membranes through electrodeposition, freeze-drying and peeling from smooth and flat metal substrates. The physical cross-linking process carried out in an aqueous environment at room temperature strictly controls the material properties through processing parameters. Due to the relatively simple equipment and short manufacturing time, it is compatible with industrial upgrades. Using the porous substrate of additive manufacturing as the skeleton and template, electro-growth forms polymer cryogel, which can realize additive manufacturing of personalized membranes. The semi-permeability of the composite GBR membrane is achieved by adjusting the electrodeposition parameters to change the coverage of the polymer cryogel on the porous substrate. Summary of the invention

[0005] The present invention aims to solve the technical problems of insufficient bone mass, poor material rigidity, secondary surgery and personalized manufacturing challenges of GBR membranes, and provides a method for preparing a semi-permeable personalized composite guided bone regeneration membrane. The composite GBR membrane prepared by the present invention has a tailor-made structure, significant osteogenesis and antibacterial ability, and realizes the functional requirement of semi-permeability of personalized composite GBR membranes; compared with the complex preparation process of clinical GBR membranes, the preparation method of the present invention is simple and easy, with a short manufacturing time, and is compatible with industrial upgrading.

[0006] A method for preparing a semi-permeable personalized composite guided bone regeneration membrane comprises the following steps:

[0007] S1. Use CT scanning technology to obtain the patient's alveolar bone morphology and design a personalized GBR membrane model;

[0008] S2. Based on the surface characteristics of the personalized GBR membrane model, multiple lattice units are used for filling to construct a porous GBR membrane model with a complete lattice structure;

[0009] S3, importing the constructed porous GBR membrane model into the laser selective melting additive manufacturing equipment software, the forming direction is determined according to the principle of minimum Z-axis height, the model adopts a point support structure, and the corresponding forming process parameters are set to manufacture the metal porous GBR membrane;

[0010] S4, using the metal porous GBR membrane formed in step S3 as a substrate, coating the polymer cryogel on the metal porous GBR membrane by electrodeposition technology to prepare a composite GBR membrane of metal and polymer;

[0011] S5. By optimizing the polymer concentration, electric field and electrodeposition time during the electrodeposition process, the porous structure characteristics of the composite GBR membrane are regulated so that the average pore size of the composite GBR membrane is larger than the size of the protein but smaller than the size of the fibroblasts, thereby achieving the semi-permeability function of the composite GBR membrane.

[0012] The present application discloses a method for preparing a semi-permeable personalized composite guided bone regeneration membrane. By using CT scanning technology to accurately obtain the morphology of the patient's alveolar bone, a personalized GBR membrane model is designed. The personalized GBR membrane model can fit the patient's alveolar bone morphology more specifically, which is beneficial to reducing the risk of patient discomfort and infection. The metal porous GBR membrane is manufactured by laser selective melting additive manufacturing technology, which improves the accuracy and quality of the membrane and reduces material waste, which is in line with the development of modern manufacturing technology. The polymer cryogel is coated on the metal porous GBR membrane by electrodeposition technology, and a composite GBR membrane of metal and polymer is innovatively prepared, which enhances the functionality and adaptability of the composite GBR membrane. By precisely regulating the porous structural characteristics of the composite GBR membrane, the average pore size of the membrane is larger than the protein size and smaller than the fibroblast size, giving the composite GBR membrane a semi-permeable function, which is beneficial to the permeation of nutrients and the migration of cells, while preventing the invasion of bacteria. By optimizing the key parameters in the electrodeposition process and accurately controlling the pore size of the composite GBR membrane, the fine regulation of the functional characteristics of the membrane is achieved, and the performance and clinical application effect of the composite GBR membrane are improved. Compared with the complex preparation process of traditional clinical GBR membrane, the preparation method of the present invention is simple and easy, with a short manufacturing time, reduced production cost and improved production efficiency.

[0013] In any of the above technical solutions, in step S1, the personalized GBR membrane model includes the shape and contour of the patient's alveolar bone edge, and the position and size of the bone defect area obtained by CT scanning technology.

[0014] The shape and contour of the patient's alveolar bone edge, as well as the position and size of the bone defect area obtained through CT scanning technology can ensure that the GBR membrane model accurately matches the patient's actual alveolar bone structure, improve the personalization and adaptability of treatment, and reduce the risk of postoperative complications such as infection, displacement or rejection.

[0015] In any of the above technical solutions, the lattice unit includes a symmetrical bar lattice unit with nodes.

[0016] In any of the above technical solutions, a plurality of the lattice units are connected via nodes.

[0017] In any of the above technical solutions, the shapes of the plurality of lattice units are one or more of body-centered cubic (BCC), regular octahedron cube (ROC), body-centered and face-centered cubic (BFCC), face-centered cubic (FCC), regular hexahedron (Cubic), cubic octahedron (Cuboctahedron), truncated octahedron (Truncated octahedron), regular dodecahedron (Dodecahedron), rhombic dodecahedron (Rhombic dodecahedron), and regular icosahedron (Icosahedron).

[0018] The use of a symmetrical rod lattice with nodes helps to improve the mechanical properties of the composite GBR membrane, enhance the stability of the structure, and reduce deformation under external effects. At the same time, it can adapt to different loading conditions and environmental conditions, showing strong adaptability and durability.

[0019] In any of the above technical solutions, in step S3, the forming process parameters include scanning speed, laser power, spot diameter, and scanning spacing.

[0020] By accurately setting the forming process parameters such as scanning speed, laser power, spot diameter and scanning spacing, the metal melting and solidification behavior during the selective laser melting (SLM) process can be finely controlled to obtain a high-quality metal porous GBR membrane model.

[0021] In any of the above technical solutions, it also includes a process of placing the GBR membrane model. During the process of placing the porous GBR membrane model, the GBR membrane model is staggered in the Z-axis direction.

[0022] By staggering the GBR membrane models in the Z-axis direction, the model overlap phenomenon in the Z-axis direction can be avoided, thereby avoiding defects in the metal porous GBR membrane model during the forming process, such as holes and unfused areas, which may affect the integrity and function of the GBR membrane.

[0023] In any of the above technical solutions, in step S3, the metal material used in the metal porous GBR membrane includes one of a degradable medical metal and a non-degradable medical metal.

[0024] By using degradable medical metals or non-degradable medical metals as the metal material of the metal porous GBR membrane, the most suitable material can be selected according to the specific clinical needs and the patient's recovery. This diversity enables the GBR membrane to adapt to different treatment scenarios and patient conditions. The use of medical metals with good biocompatibility and bioactivity can reduce the risk of postoperative complications such as infection, inflammation, and tissue reactions caused by materials.

[0025] In any of the above technical solutions, the degradable metal includes one or more of zinc, magnesium, iron and their alloys, and the non-degradable metal includes one or more of titanium and titanium alloys, cobalt-chromium alloys and stainless steel.

[0026] By using degradable medical metals such as zinc, magnesium, iron and their alloys, as well as non-degradable medical metals such as titanium and titanium alloys, cobalt-chromium alloys, and stainless steel as materials for metal porous GBR membranes, biocompatibility with human tissues is ensured, reducing patients' rejection of implanted materials. The introduction of degradable medical metals can be gradually absorbed by the human body over time, while releasing elements that promote bone cell growth and accelerate the bone regeneration process. The use of non-degradable medical metals can provide the necessary mechanical strength and stability for metal porous GBR membranes.

[0027] In any of the above technical solutions, in step S4, the material of the polymer cryogel includes one of collagen, silk fibroin, chitosan, gelatin or a composite thereof.

[0028] Biodegradable polymers such as collagen, silk fibroin, chitosan, and gelatin have good biocompatibility and biodegradability. Coating these polymers on the metal GBR membrane can effectively regulate the permeability of the material. At the same time, it can reduce the host's immune response to the implanted material and reduce the risk of inflammation, thereby improving the safety and reliability of the GBR membrane.

[0029] In any of the above technical solutions, in step S5, the optimization of the electrodeposition process is to select the preparation ratio of the polymer solution, the electric field parameters required for electrodeposition, and the electrodeposition time parameters.

[0030] By optimizing the electrodeposition process and precisely controlling the preparation ratio of the polymer solution, the electric field parameters and the electrodeposition time parameters, the physical and chemical properties of the composite GBR membrane, including its semi-permeability, mechanical strength and biocompatibility, can be finely controlled.

[0031] In any of the above technical solutions, in step S5, the composite GBR membrane allows protein transfer but does not allow fibroblasts to pass through.

[0032] The function of allowing protein transfer means that the composite GBR membrane can selectively allow the nutrients and biomolecules required for bone growth to pass through, thereby promoting the bone regeneration process in the bone defect area. Blocking the passage of fibroblasts enables the composite GBR membrane to ensure that the bone regeneration process is not interfered with by non-osteoblasts, which may migrate to the bone defect area and interfere with normal bone regeneration. Through the semi-permeable function of the composite GBR membrane, not only the bone regeneration microenvironment is optimized, but also the safety and effectiveness of the treatment are improved.

[0033] In any of the above technical solutions, in step S5, the composite GBR membrane has osteogenic ability and antibacterial ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the preparation method of the present invention;

[0035] Figure 2 The personalized guided bone regeneration membrane model of Example 1 of the present invention;

[0036] Figure 3 The porous guided bone regeneration membrane model constructed in Example 1 of the present invention;

[0037] Figure 4 A flow chart of preparing a composite guided bone regeneration membrane according to Example 1 of the present invention;

[0038] Figure 5 The structural morphology of a semi-permeable personalized composite guided bone regeneration membrane obtained in Example 1 of the present invention: (a) a representative digital photo; (b) a combined image of a fluorescence microscope and an optical microscope; (c) to (d) SEM images of the composite membrane;

[0039] Figure 6 The metal / polymer composite guided bone regeneration membrane obtained in Example 1 of the present invention;

[0040] Figure 7 The following are mapping diagrams of energy dispersive spectrometer (EDS) analysis of the composite guided bone regeneration membrane obtained in Example 1 of the present invention: (a) mapping diagram of Zn / O / C / N elements; (b) mapping diagram of Zn elements; (c) mapping diagram of O elements; (d) mapping diagram of N elements.

[0041] Figure 8 SEM images of the biodegradation of the composite guided bone regeneration membrane obtained in Example 1 of the present invention immersed in simulated body fluid: (a) SEM image after immersion for 28 days; (b) SEM image after immersion for 60 days.

[0042] Fig. 9 This is an EDS mapping diagram of the composite guided bone regeneration membrane obtained in Example 1 of the present invention immersed in simulated body fluid for 60 days.

[0043] Fig.10 Model diagrams used in Example 2 of the present invention: (a) a model diagram for testing the nutrient transfer characteristics of the membrane; (b) a model diagram for evaluating the inhibition of fibroblast infiltration.

[0044] Fig.11The semi-permeability result diagram of a semi-permeable personalized composite guided bone regeneration membrane obtained in Example 2 of the present invention: (a) the permeation rate of BSA through the membrane using different electrodeposition times; (b) the inhibition rate of fibroblast permeation of the membrane using different electrodeposition times.

[0045] Fig.12 The results of the osteogenic ability of a semi-permeable personalized composite guided bone regeneration membrane obtained in Example 3 of the present invention are as follows: (a) staining with alkaline phosphatase (ALP) after 7 days of cell culture; (b) staining with alizarin red (AR) after 14 days of cell culture; (c) staining with alizarin red (AR) after 21 days of cell culture.

[0046] Fig.13 The antibacterial ability result diagram of a semi-permeable personalized composite guided bone regeneration membrane obtained in Example 3 of the present invention: (a) a representative digital photo of the antibacterial area; (b) a SEM image. DETAILED DESCRIPTION

[0047] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0049] The following describes the method for preparing the semi-permeable personalized composite guided bone regeneration membrane according to some embodiments of the present invention with reference to the accompanying drawings.

[0050] The design idea and principle of the present invention are as follows: first, the alveolar bone morphology of the patient is obtained by using CT scanning technology to design a personalized GBR membrane model; then, based on the surface characteristics of the personalized GBR membrane model, a plurality of lattice units are used for filling to construct a porous GBR membrane model with a complete lattice structure; then, the constructed porous GBR membrane model is imported into the laser selective melting additive manufacturing equipment software, the forming direction is determined according to the principle of the minimum Z-axis height, the model adopts a point support structure, and the corresponding forming process parameters are set to manufacture a metal porous GBR membrane model; then, the above-mentioned formed metal porous GBR membrane is used as a substrate, and the polymer cryogel is coated on the metal porous GBR membrane by electrodeposition technology to prepare a composite GBR membrane of metal and polymer; finally, by optimizing the polymer concentration, electric field and electrodeposition time in the electrodeposition process, the porous structure characteristics of the composite GBR membrane are regulated so that the average pore size is larger than the size of the protein and smaller than the size of the fibroblasts, thereby achieving the semi-permeability of the personalized composite GBR membrane.

[0051] The technical solution of the present invention will be described in detail below in conjunction with the specific implementation and the accompanying drawings of the specification. Among them, a process for preparing a semi-permeable personalized composite guided bone regeneration membrane is as follows Figure 1 shown.

[0052] Example 1

[0053] S1. Use CT scanning technology to obtain the patient's alveolar bone morphology and design a personalized GBR membrane model.

[0054] Among them, the patient's alveolar bone morphology is Figure 2 As shown in (a), the GBR solid model obtained by CT scanning technology is as follows Figure 2 (b) as shown.

[0055] S2. Based on the surface characteristics of the personalized GBR membrane model, multiple lattice units are used for filling to construct a porous GBR membrane model with a complete lattice structure.

[0056] Among them, the porous GBR membrane model constructed is as follows Figure 3 The body-centered cubic (BCC) lattice unit is used as the filling unit cell, and the parameterized model of the BCC filling unit cell is constructed. The boundary size of the body-centered cubic is 1.2 mm × 1.2 mm, and the diameter of the support column is 0.2 mm.

[0057] Among them, the body-centered cubic is a symmetrical bar lattice unit with nodes, and the lattice units are connected by nodes.

[0058] S3. The constructed porous GBR membrane model is imported into the laser selective melting additive manufacturing equipment software. The forming direction is determined according to the principle of minimum Z-axis height. The model adopts a point support structure and sets corresponding forming process parameters to manufacture a metal porous GBR membrane.

[0059] Among them, the porous GBR membrane model was converted into STL format and imported into the laser selective melting additive manufacturing equipment software to set the processing parameters. The SLM forming metal material was selected as degradable metal pure zinc (Zn), the scanning speed was 600mm / s, the laser power was 80W, the spot diameter was 0.07mm, and the scanning spacing was 0.05mm. When placing the GBR membrane model, avoid model overlap in the Z-axis direction.

[0060] S4. The Zn metal porous GBR membrane model formed above is used as a substrate, and the polymer cryogel is coated on the metal substrate by electrodeposition technology to prepare a metal / polymer composite GBR membrane. The preparation process using chitosan (CS) and gelatin (G) solution as polymers is as follows: Figure 4 As shown, the specific steps are as follows:

[0061] As shown in equation (1), chitosan initially dissolves in an acidic aqueous solution due to the protonation of the amine groups. When gelatin is dissolved in the chitosan solution, the electrostatic interaction between the -NH3+ groups on chitosan and the -COO- groups on gelatin leads to the formation of a positively charged CSG colloidal polyelectrolyte complex.

[0062] During the electrodeposition process, water electrolysis occurs at the cathode (zinc substrate), resulting in the generation of hydrogen bubbles and an increase in the local pH value, as shown in equation (2). The electric field can induce the charged CSG colloidal polyelectrolyte complex to migrate toward the cathode, thereby enriching the concentration in the solution. In this high pH region, the protonated amine groups of chitosan in the polyelectrolyte complex may lose their charge.

[0063] The CSG polyelectrolyte complex transforms from a sol to a gel state by physically cross-linking by trapping hydrogen bubbles on the Zn substrate, thereby assembling into a conformal electrogel, as shown in Eq. (3).

[0064] CS–NH2+H3O+→CS–NH3++H2O (1)

[0065] 2H2O+2e-→H2+2OH-(Cathode / Zn substrate) (2)

[0066] CS–NH3++OH-→CS–NH2+H2O(Cathode / Zn substrate) (3)

[0067] S5. By optimizing the polymer concentration, electric field and electrodeposition time during the electrodeposition process, the porous structure characteristics of the composite GBR membrane are regulated so that the average pore size of the composite GBR membrane is larger than the size of the protein but smaller than the size of the fibroblasts, thereby achieving the semi-permeability function of the composite GBR membrane. The optimization steps are as follows:

[0068] Prepare chitosan solution and gelatin precursor solution concentrations. Dissolve chitosan in 0.06M HCl solution to prepare a 10mg / ml chitosan solution. Dissolve gelatin powder in chitosan solution and adjust the pH to 4 to prepare a chitosan / gelatin precursor solution with a gelatin concentration of 1mg / ml.

[0069] The electric field parameters required for electrodeposition were set, and a DC power supply applied an electric field of 5 V / cm.

[0070] The electrodeposition time was 1 min.

[0071] Among them, the structural morphology of the personalized, semi-permeable metal-polymer composite GBR membrane obtained with an electrodeposition time of 1 min is shown in the figure below: Figure 5 shown. Figure 5 In (a), the conformal CSG gel is evenly covered on the Zn substrate with appropriate thickness; Figure 5 In (b), chitosan macromolecules exhibit blue autofluorescence, which effectively illustrates the conformal and porous morphology of CSG cryogel; Figure 5 In (c) to (d), the CSG cryogel covers the entire Zn substrate to form a uniform sponge-like microstructure without obvious cracks.

[0072] After electrodeposition, the Zn samples containing conformal chitosan / gelatin were taken out and frozen in liquid nitrogen.

[0073] Among them, the composite GBR film after electrodeposition is as follows Figure 6 shown.

[0074] The composite GBR film obtained in Example 1 was analyzed by energy dispersive spectrometer (EDS) as shown in the following figure: Figure 7 As shown. Figure 7 In (a) to (b), the Zn element is consistent with the support morphology of the Zn substrate, and the distribution of C, O, and N elements in (c) to (e) in the EDS images indicates that the CSG cryogel completely covers the Zn substrate.

[0075] The biodegradation of the composite GBR membrane obtained in Example 1 after immersion in simulated body fluid is as follows: Figure 8 As shown. Figure 8 In (a), (a1) shows that the integrity of the CSG / Zn composite GBR membrane remains unchanged after immersion in simulated body fluid for 28 days, while (a2) to (a4) reflect some cracks filled with granular degradation products on the polymer cryogel; Figure 8 In (b), some corrosion edges are obvious in (b1), but the structural integrity of the CSG / Zn composite GBR membrane remains intact after immersion in simulated body fluid for 60 days, e.g. Fig. 9 (h) The N element EDS spectrum shows that the polymer cryogel still partially exists even after 60 days. Figure 8 (b2) to (b4) show that the cryogel morphology has more cracks but is completely covered by coral-like inorganic degradation products.

[0076] Example 2

[0077] The semi-permeability of the semi-permeable personalized composite guided bone regeneration membrane of the present invention is evaluated by the following steps:

[0078] S1. Prepare CSG / Zn composite GBR films with different electrodeposition times using the preparation method of Example 1.

[0079] Among them, the different electrodeposition times prepared are 5s, 1min, 2min, and 5min respectively.

[0080] S2. Evaluation of nutrient transfer characteristics by bovine serum albumin (BSA) permeability.

[0081] Among them, the molecular weight of BSA is 69,000, which is larger than that of most nutrients and can be used as a model protein; at the same time, the BSA concentration used is 70 mg / mL, which is similar to the concentration in total serum protein.

[0082] In order to measure the nutrient transfer capacity, the Fig.10 (a) The model shown, the membrane sample is sandwiched between two steam-sterilized hollow stainless steel cylinders (outer diameter 14mm, inner diameter 12mm, height 8mm), wrapped with plastic wrap, and then placed in a 12-well plate. The membrane sample for measurement is first hydrated with BSA solution (70mg / mL), and then 1mL of BSA solution is added to the cylinder above the membrane. After 30 minutes, all the BSA solution is transferred, and the protein concentration that permeates the membrane into the well is determined using the BCA protein quantification kit.

[0083] S3. The inhibition of fibroblast infiltration was evaluated by calculating the inhibition rate of fibroblast permeation of the composite membrane.

[0084] Here, a similar device as step S2 was used to evaluate the inhibitory effect of the composite GBR membrane on fibroblasts, and the model was as follows: Fig.10(b) As shown. NIH3T3 cells (mouse embryonic fibroblasts) were cultured in a DEME medium containing 10% fetal bovine serum in a humidified environment of 5% CO2 and 37°C. The membrane sample for measurement was first hydrated with DEME, and when the cells were prepared into a suspension of 1×106 / ml using DEME, 1 ml of the cell suspension was added to the columnar model. After 4 hours, the cell permeation rate was measured by counting the number of cells in the wells under the membrane using a cell counter after trypsin digestion.

[0085] Example 2 Evaluation of the semi-permeability of a personalized, semi-permeable metal-polymer composite GBR membrane Fig.11 shown. Fig.11 In (a), the permeability of BSA was always above 85%, and there was no significant difference between the different electrodeposition time groups, indicating that all membranes had effective nutrient transfer capabilities; Fig.11 In (b), as the electrodeposition time increases, the inhibition first increases and then decreases, reaching a peak of 100% at 1 minute.

[0086] Example 3

[0087] The osteogenic ability and antibacterial ability of the semi-permeable personalized composite guided bone regeneration membrane of the present invention are evaluated by the following steps:

[0088] S1. Prepare a CSG / Zn composite GBR film with an electrodeposition time of 1 min by the preparation method of Example 1.

[0089] S2. The osteogenic property of the composite GBR membrane was evaluated by alkaline phosphatase (ALP) staining and Alizarin red (AR) staining.

[0090] Among them, Ti was used as the negative control group, Ti+osteoblast induction solution was used as the positive control group, and CSG / Zn composite GBR membrane was used as the experimental group. The extracts of the above different samples were extracted to culture bone marrow mesenchymal stem cells. After culturing the cells for 7 days, the cells were fixed in 4% paraformaldehyde and ALP staining was performed using 5-bromo-4-chloro-3-indolyl phosphate (BCIP) / nitro blue tetrazolium (NBT). Observation was performed using an optical microscope. After culturing the cells for 14 and 21 days, the cells were fixed in 95% ethanol for 30 minutes, washed with deionized water, and then stained with 0.1% alizarin red for 1 hour at room temperature. Observation was performed using an optical microscope.

[0091] S3. The antibacterial properties of the composite GBR membrane against Staphylococcus aureus were evaluated by diffusion method.

[0092] Among them, titanium disk was used as a control. Staphylococcus aureus was cultured in Muller-Hinton broth with a concentration of about 1×108 colony-forming units mL -1. The samples (n=3) were placed under ultraviolet irradiation for 2 hours for disinfection. Pure titanium with the same particle size was used as the control group. 100 μL of the dispersed bacterial suspension was inoculated, and the bacterial suspension was evenly spread on the entire surface of the Muller-Hinton agar plate with a sterile cotton swab, and then the sterile sample was placed. After incubation at 37°C for 24 hours, the diameter of the inhibition zone was observed and measured. The samples co-cultured with Staphylococcus aureus were gently washed 3 times with PBS, fixed in 2.5% glutaraldehyde for 20 minutes, and then dehydrated in an ethanol gradient (5 minutes in 70%, 80%, 90%, and 96%, respectively, and 10 minutes twice in 100% ethanol), and dried in air. The surface morphology was then observed using a scanning electron microscope (SEM).

[0093] Example 3 Evaluation of the osteogenic ability of a semi-permeable composite guided bone regeneration membrane Fig.12 As shown in the figure, the ALP staining and alizarin red staining of the CSG / Zn composite GBR membrane group were higher than those of the Ti group without osteoinduction, and slightly lower than those of the Ti group with osteoinduction. This shows that the CSG / Zn composite GBR membrane has effective osteoinduction ability.

[0094] Example 3 Evaluation of the antibacterial ability of a semi-permeable personalized composite guided bone regeneration membrane Fig.13 shown. Fig.13 In (a), the antibacterial zone of the CSG / Zn composite GBR membrane group that was not immersed or immersed in simulated body fluid for 60 days was larger than that of the Ti group. Fig.13 In (b), scanning electron microscopy showed that the Staphylococcus aureus on the Ti surface was evenly distributed and uniform in size, and no biofilm rupture was observed; while the number of Staphylococcus aureus in the CSG / Zn composite GBR membrane group that was not immersed in simulated body fluids was significantly reduced, and the biofilm was ruptured; the number of Staphylococcus aureus in the CSG / Zn composite GBR membrane that was immersed in simulated body fluids for 60 days was significantly less than that in the Ti group, slightly more than that in the non-immersed group, and the biofilm was also ruptured. This shows that the CSG / Zn composite GBR membrane has effective antibacterial ability before and after immersion in simulated body fluids.

[0095] Example 4

[0096] like Figure 1 As shown, a method for preparing a semi-permeable personalized composite guided bone regeneration membrane comprises the following steps:

[0097] S1. Use CT scanning technology to obtain the patient's alveolar bone morphology and design a personalized GBR membrane model;

[0098] S2. Based on the surface characteristics of the personalized GBR membrane model, multiple lattice units are used for filling to construct a porous GBR membrane model with a complete lattice structure;

[0099] S3, importing the constructed porous GBR membrane model into the laser selective melting additive manufacturing equipment software, the forming direction is determined according to the principle of minimum Z-axis height, the model adopts a point support structure, and the corresponding forming process parameters are set to manufacture the metal porous GBR membrane;

[0100] S4, using the metal porous GBR membrane formed in step S3 as a substrate, coating the polymer cryogel on the metal porous GBR membrane by electrodeposition technology to prepare a composite GBR membrane of metal and polymer;

[0101] S5. By optimizing the polymer concentration, electric field and electrodeposition time during the electrodeposition process, the porous structure characteristics of the composite GBR membrane are regulated so that the average pore size of the composite GBR membrane is larger than the size of the protein but smaller than the size of the fibroblasts, thereby achieving the semi-permeability function of the composite GBR membrane.

[0102] The present application discloses a method for preparing a semi-permeable personalized composite guided bone regeneration membrane. By using CT scanning technology to accurately obtain the morphology of the patient's alveolar bone, a personalized GBR membrane model is designed. The personalized GBR membrane model can fit the patient's alveolar bone morphology more specifically, which is beneficial to reducing the risk of patient discomfort and infection. The metal porous GBR membrane is manufactured by laser selective melting additive manufacturing technology, which improves the accuracy and quality of the membrane and reduces material waste, which is in line with the development of modern manufacturing technology. The polymer cryogel is coated on the metal porous GBR membrane by electrodeposition technology, and a composite GBR membrane of metal and polymer is innovatively prepared, which enhances the functionality and adaptability of the composite GBR membrane. By precisely regulating the porous structural characteristics of the composite GBR membrane, the average pore size of the membrane is larger than the protein size and smaller than the fibroblast size, giving the composite GBR membrane a semi-permeable function, which is beneficial to the permeation of nutrients and the migration of cells, while preventing the invasion of bacteria. By optimizing the key parameters in the electrodeposition process and accurately controlling the pore size of the composite GBR membrane, the fine regulation of the functional characteristics of the membrane is achieved, and the performance and clinical application effect of the composite GBR membrane are improved. Compared with the complex preparation process of traditional clinical GBR membrane, the preparation method of the present invention is simple and easy, with a short manufacturing time, reduced production cost and improved production efficiency.

[0103] In any of the above technical solutions, in step S1, the personalized GBR membrane model includes the shape and contour of the patient's alveolar bone edge obtained by CT scanning technology, and the position and size of the bone defect area.

[0104] The shape and contour of the patient's alveolar bone edge, as well as the position and size of the bone defect area obtained through CT scanning technology can ensure that the GBR membrane model accurately matches the patient's actual alveolar bone structure, improve the personalization and adaptability of treatment, and reduce the risk of postoperative complications such as infection, displacement or rejection.

[0105] In any of the above technical solutions, the lattice unit includes a symmetrical bar lattice unit with nodes.

[0106] In any of the above technical solutions, a plurality of the lattice units are connected via nodes.

[0107] In any of the above technical solutions, the shapes of the plurality of lattice units are one or more of body-centered cubic (BCC), regular octahedron cube (ROC), body-centered and face-centered cubic (BFCC), face-centered cubic (FCC), regular hexahedron (Cubic), cubic octahedron (Cuboctahedron), truncated octahedron (Truncated octahedron), regular dodecahedron (Dodecahedron), rhombic dodecahedron (Rhombic dodecahedron), and regular icosahedron (Icosahedron).

[0108] The use of a symmetrical rod lattice with nodes helps to improve the mechanical properties of the composite GBR membrane, enhance the stability of the structure, and reduce deformation under external effects. At the same time, it can adapt to different loading conditions and environmental conditions, showing strong adaptability and durability.

[0109] In any of the above technical solutions, in step S3, the forming process parameters include scanning speed, laser power, spot diameter, and scanning spacing.

[0110] By accurately setting the forming process parameters such as scanning speed, laser power, spot diameter and scanning spacing, the metal melting and solidification behavior during the selective laser melting (SLM) process can be finely controlled to obtain a high-quality metal porous GBR membrane model.

[0111] In any of the above technical solutions, it also includes a process of placing the GBR membrane model. During the process of placing the porous GBR membrane model, the GBR membrane model is staggered in the Z-axis direction.

[0112] By staggering the GBR membrane models in the Z-axis direction, the model overlap phenomenon in the Z-axis direction can be avoided, thereby avoiding defects in the metal porous GBR membrane model during the forming process, such as holes and unfused areas, which may affect the integrity and function of the GBR membrane.

[0113] In any of the above technical solutions, in step S3, the metal material used in the metal porous GBR membrane includes one of a degradable medical metal and a non-degradable medical metal.

[0114] By using degradable medical metals or non-degradable medical metals as the metal material of the metal porous GBR membrane, the most suitable material can be selected according to the specific clinical needs and the patient's recovery. This diversity enables the GBR membrane to adapt to different treatment scenarios and patient conditions. The use of medical metals with good biocompatibility and bioactivity can reduce the risk of postoperative complications such as infection, inflammation, and tissue reactions caused by materials.

[0115] In any of the above technical solutions, the degradable metal includes one or more of zinc, magnesium, iron and their alloys, and the non-degradable metal includes one or more of titanium and titanium alloys, cobalt-chromium alloys and stainless steel.

[0116] By using degradable medical metals such as zinc, magnesium, iron and their alloys, as well as non-degradable medical metals such as titanium and titanium alloys, cobalt-chromium alloys, and stainless steel as materials for metal porous GBR membranes, biocompatibility with human tissues is ensured, reducing patients' rejection of implanted materials. The introduction of degradable medical metals can be gradually absorbed by the human body over time, while releasing elements that promote bone cell growth and accelerate the bone regeneration process. The use of non-degradable medical metals can provide the necessary mechanical strength and stability for metal porous GBR membranes.

[0117] In any of the above technical solutions, in step S4, the material of the polymer cryogel includes one of collagen, silk fibroin, chitosan, gelatin or a composite thereof.

[0118] Biodegradable polymers such as collagen, silk fibroin, chitosan, and gelatin have good biocompatibility and biodegradability. Coating these polymers on the metal GBR membrane can effectively regulate the permeability of the material. At the same time, it can reduce the host's immune response to the implanted material and reduce the risk of inflammation, thereby improving the safety and reliability of the GBR membrane.

[0119] In any of the above technical solutions, in step S5, optimizing the electrodeposition process is to select the preparation ratio of the polymer solution, the electric field parameters required for electrodeposition, and the electrodeposition time parameters.

[0120] By optimizing the electrodeposition process and precisely controlling the preparation ratio of the polymer solution, the electric field parameters and the electrodeposition time parameters, the physical and chemical properties of the composite GBR membrane, including its semi-permeability, mechanical strength and biocompatibility, can be finely controlled.

[0121] In any of the above technical solutions, in step S5, the composite GBR membrane allows protein transfer but does not allow fibroblasts to pass through.

[0122] The function of allowing protein transfer means that the composite GBR membrane can selectively allow the nutrients and biomolecules required for bone growth to pass through, thereby promoting the bone regeneration process in the bone defect area. Blocking the passage of fibroblasts enables the composite GBR membrane to ensure that the bone regeneration process is not interfered with by non-osteoblasts, which may migrate to the bone defect area and interfere with normal bone regeneration. Through the semi-permeable function of the composite GBR membrane, not only the bone regeneration microenvironment is optimized, but also the safety and effectiveness of the treatment are improved.

[0123] In any of the above technical solutions, in step S5, the composite GBR membrane has osteogenic ability and antibacterial ability.

[0124] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0125] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a semi-permeable personalized composite guided bone regeneration membrane, characterized in that: The following steps are involved: S1. Use CT scanning technology to obtain the patient's alveolar bone morphology and design a personalized GBR membrane model; S2. Based on the surface characteristics of the personalized GBR membrane model, multiple lattice units are used for filling to construct a porous GBR membrane model with a complete lattice structure; S3, importing the constructed porous GBR membrane model into the laser selective melting additive manufacturing equipment software, the forming direction is determined according to the principle of minimum Z-axis height, the model adopts a point support structure, and the corresponding forming process parameters are set to manufacture the metal porous GBR membrane; S4, using the metal porous GBR membrane formed in step S3 as a substrate, coating the polymer cryogel on the metal porous GBR membrane by electrodeposition technology to prepare a composite GBR membrane of metal and polymer; S5. By optimizing the polymer concentration, electric field and electrodeposition time during the electrodeposition process, the porous structure characteristics of the composite GBR membrane are regulated so that the average pore size of the composite GBR membrane is larger than the size of the protein but smaller than the size of the fibroblasts, thereby achieving the semi-permeability function of the composite GBR membrane.

2. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In step S1, the personalized GBR membrane model includes the shape and contour of the patient's alveolar bone edge obtained by CT scanning technology, and the position and size of the bone defect area.

3. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: The lattice unit comprises a symmetrical bar lattice unit having nodes; and / or a plurality of the lattice units are connected via nodes; And / or the shapes of the plurality of lattice units are one or more of body-centered cube, regular octahedron cube, body-centered and face-centered cube, face-centered cube, regular hexahedron, cuboctahedron, truncated octahedron, regular dodecahedron, rhombic dodecahedron, and regular icosahedron.

4. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In the step S3, the forming process parameters include scanning speed, laser power, spot diameter, and scanning spacing; And / or also includes a process of placing the GBR membrane model, during which the porous GBR membrane model is placed, the GBR membrane model is staggered in the Z-axis direction.

5. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In the step S3, the metal material used in the metal porous GBR membrane includes one of a degradable medical metal and a non-degradable medical metal.

6. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 5, characterized in that: The degradable medical metal includes one or more of zinc, magnesium, iron and alloys thereof, and the non-degradable medical metal includes one or more of titanium and titanium alloys, cobalt-chromium alloys and stainless steel.

7. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In step S4, the material of the polymer cryogel includes one of collagen, silk fibroin, chitosan, gelatin or a composite thereof.

8. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In the step S5, the optimization of the electrodeposition process is to select the preparation ratio of the polymer solution, the electric field parameters required for electrodeposition, and the electrodeposition time parameters.

9. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In step S5, the composite GBR membrane allows protein transfer but does not allow fibroblasts to pass through.

10. The method for preparing a semi-permeable personalized composite guided bone regeneration membrane according to claim 1, characterized in that: In the step S5, the composite GBR membrane has osteogenic ability and antibacterial ability.

Citation Information

Patent Citations

  • Self-mineralized GBR membrane and preparation method thereof

    CN115518206A

  • Thin-wall curved-surface porous part design method oriented to selective laser melting technology

    CN116070370A

  • Dental bone-guided regeneration membrane and preparation method thereof

    CN116077740A

  • Electronic device

    KR102450478B1